2021
DOI: 10.1159/000521582
|View full text |Cite
|
Sign up to set email alerts
|

IgA Nephropathy and Atypical Anti-GBM Disease: A Rare Dual Pathology in a Pediatric Rapidly Progressive Glomerulonephritis

Abstract: Introduction: Anti-GBM nephritis in the pediatric age group is exceedingly rare with concurrent additional pathologies being even rarer. Tissue diagnosis requires a combination of crescentic histomorphology, immunofluorescence showing “Paint brush stroke” pattern of linear IgG or rarely IgA and serum anti-GBM antibodies subject to the disease course and treatment. The authors describe one such case with a dual pathology involving IgA nephropathy and atypical anti-GBM disease. Case presentation: A thirteen-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The previous studies have shown mixed picture with small studies reporting poor prognosis [7], while a large study reported better prognosis and outcomes of double-positive patients [12]. In 2 (14.2%) of our renal biopsied patients have concomitant mesangial IgA positivity along with linear IgG; this mesangial IgA positivity along with linear IgG positivity was also seen in 4% patients of the Zahir et al cohort and multiple other studies also [13, 18, 19].…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…The previous studies have shown mixed picture with small studies reporting poor prognosis [7], while a large study reported better prognosis and outcomes of double-positive patients [12]. In 2 (14.2%) of our renal biopsied patients have concomitant mesangial IgA positivity along with linear IgG; this mesangial IgA positivity along with linear IgG positivity was also seen in 4% patients of the Zahir et al cohort and multiple other studies also [13, 18, 19].…”
Section: Discussionsupporting
confidence: 46%
“…Nine (60%) patients were in the 6th decade of their life, and rest in 2nd and 3rd decades. The median duration of symptoms onset to nephrologist opinion was 15 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) days. The extrarenal manifestations were seen in the respiratory system [3 (20%)], otorhinolaryngological system (2 [3.3%]), and neurological system [1 (6%)].…”
Section: Resultsmentioning
confidence: 99%
“… 43/F [ 23 ] Focal crescents and endocapillary hypercellularity IgG (+); IgA (-); IgM (-); C3 (-); C4 (-); C1q (-); IgG1 (+);IgG4 (+); IgG2 (-);IgG3 (-); kappa (+); and lambda (+). linear deposition Negative Some FPE 13/F [ 24 ] Mesangial proliferation, focal crescents, some globally or segmentally sclerosed glomeruli IgG (+); IgA (+); IgM (-); C3 (+);C1q (-); IgG1 (+);IgG4 (+);kappa (+); and lambda (+). linear deposition Negative NA 4/F [ 25 ] Subtle segmental scars, segmental endocapillary hypercellularity, and cellular crescent IgG (+);IgA (-); IgM (-); C3 (-); C1q (-).…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenesis of IgAN is characterized by IgA-containing immune complexes passing through the glomerular capillary walls and depositing extensively in the mesangium [ 11 ]. It has been suggested that epitopes are isolated under normal circumstances and exposed following some physicochemical disruption, which then allows the initiation of immune response [ 17 ]. There was one hypothesis that IgA-related immune complexes might promote immunologic and inflammatory activities, leading to conformational changes and exposure of GBM antigens resulting in the development of anti-GBM autoantibodies [ 22 ].…”
Section: Discussionmentioning
confidence: 99%